Analysis and optimization-based synthesis of compliant mechanisms - Hasse, Alexander; Campanile, Lucio Flavio (Advances in Science and Technology (Volume 58), 2008)
Compliant mechanisms fulfil a desired force and displacement characteristic. The development of such structures having a defined kinematical motion and subjected to several constraints, like deformability, stiffness and activation force is highly challenging. The present work deals with a methodology for analysing compliant mechanisms considering geometrically nonlinear deformations. By assembling pre-calculated nonlinear beam elements a new beam truss approach is introduced. The accuracy and quality of the mechanical model are verified by selected examples and compared to existing methods. © 2008 Trans Tech Publications, Switzerlan
Keywords: Beam truss; Compliant mechanisms; Deformability; Displacement characteristics; Existing methods; Geometrically nonlinear; Large deflection; Mechanical models; Non-linear beams; Selected examples